PATCH: Particle Arrival Time Correlation for Heliophysics. Issue 5 (10th May 2021) - Verniero, J. L.; Howes, G. G.; Stewart, D. E.; Klein, K. G.
Abstract: The ability to understand the fundamental nature of the physics that governs the heliosphere requires spacecraft instrumentation to measure energy transfer at kinetic scales. This translates to a time cadence resolving the proton kinetic timescales, typically of the order of the proton gyrofrequency. The downlinked survey‐mode data from modern spacecraft are often much lower resolution than this criterion, meaning that the higher resolution, burst‐mode data must be captured to study an event at kinetic time scales. Telemetry restrictions, however, prohibit a sizable fraction of this burst‐mode data from being downlinked to the ground. The field‐particle correlation (FPC) technique can quantify kinetic‐scale energy transfer between electromagnetic fields and charged particles and identify the mechanisms responsible for mediating the transfer. In this study, we adapt the FPC technique for calculating wave‐particle energy transfer onboard modern spacecraft using time‐tagged particle counts simultaneous with electromagnetic field measurements. The newly developed procedure, called Particle Arrival Time Correlation for Heliophysics (PATCH), is tested using synthetic spacecraft data, where output from a gyrokinetic plasma turbulence simulation was downsampled to Parker Solar Probe (PSP) energy‐angle resolution. We assess the ability of the PATCH algorithm to recover the qualitative and quantitative features of the resulting velocity‐space signatures, such as ion‐Landau damping, that can be used to distinguish different kinetic mechanisms of particle energization. Ultimately, we demonstrate a proof‐of‐concept that the PATCH method could enable calculations of onboard wave‐particle correlations, with the intent of enhancing spacecraft data return by several orders of magnitude. Key Points: We develop a new algorithm, Particle Arrival Time Correlation for Heliophysics (PATCH), to quantify wave‐particle energy transfer onboard spacecraft We qualitatively assess how PATCH can resolve the velocity‐space signature of ion Landau damping We quantify the error of the PATCH method as the particle count rate varies